Polyvinyl alcohol-graft-polyethylene glycol hydrogels improve utility and biofunctionality of injectable collagen biomaterials. (8th June 2016) - Hartwell, Ryan; Chan, Ben; Elliott, Keenan; Alnojeidi, Hatem; Ghahary, Aziz
Abstract: Collagen-based materials have become a staple in both research and the clinic. In wound care, collagen-based materials comprise a core gamut of biological dressings and therapeutic strategies. In research, collagen-based materials are employed in everything from 3D cultures to bioprinting. Soluble collagen is well characterized to undergo fibrillation at neutral pH and 37 °C. To remain stable, a neutralized collagen solution must be maintained at 4 °C. These physical characteristics of collagen impose limitations on its utility. In our previous work, we identified that the incorporation of a simple polyvinyl alcohol:borate hydrogel could improve the rate of collagen gel fibrillation. In this work we sought to further investigate the interactions of polyvinyl alcohol blend variants, as surfactant-like polymers, in comparison with known non-polymer surfactants. To conduct our investigations scaffold variants were created using increasing concentrations of polyvinyl alcohol, differing combinations of polymers, and non-polymer surfactants Tweens 20 and 80, and TritonX-100. Activation energy for collagen fibrillation was found to significantly decrease in the presence of polyvinyl alcohols ( p   <  0.01) at and above 0.4%w/v concentration. Further, addition of polyvinyl alcohol-graft-polyethylene glycol had the greatest enhancement (2.02 fold) on the fibrillation kinetics ( p   <  0.01), wetting properties and the stability of the collagen scaffolds post-freeze drying. Our results demonstrated that the addition of polyvinyl alcohol hydrogels to a collagen solution could stabilize collagen solution such that the solution could easily be lyophilized (at pH 7) and then reconstituted with water. Cells cultured in polyvinyl alcohol scaffolds also exhibited more organized F-actin, as well as a reduced abundance of pro-collagen and α -smooth actin. In conclusion, our results demonstrate for the first time that polyvinyl alcohol, preferably polyvinyl alcohol-graft-polyethylene glycol, directly affects the physical properties of collagen and the physiology of cells cultured within improving the utility of the combined material for both research and clinic needs.